Structural and electrochemical properties of LiCoO2 prepared by combustion synthesis - Santiago, E. I.; Andrade, AVC; Paiva-Santos, C. O.; Bulhoes, LOS (Elsevier B.V., 2003)
LiCoO2 powders were prepared by combustion synthesis, using metallic nitrates as the oxidant and metal sources and urea as fuel. A small amount of the LiCoO2 phase was obtained directly from the combustion reaction, however, a heat treatment was necessary for the phase crystallization. The heat treatment was performed at the temperature range from 400 up to 700 degreesC for 12 h. The powders were characterized by X-ray diffraction (XRD), X ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and specific surface area values were obtained by BET isotherms. Composite electrodes were prepared using a mixture of LiCoO2, carbon black and poly(vinylidene fluoride) (PVDF) in the 85:10:5% w/w ratio. The electrochemical behavior of these composites was evaluated in ethylene carbonate/dimethylcarbonate solution, using lithium perchlorate as supporting electrolyte. Cyclic voltammograms showed one reversible redox process at 4.0/3.85 V and one irreversible redox process at 3.3 V for the LiCoO2 obtained after a post-heat treatment at 400 and 500 degreesC.Raman spectroscopy showed the possible presence of LiCoO2 with cubic structure for the material obtained at 400 and 500 degreesC. This result is in agreement with X-ray data with structural refinement for the LiCoO2 powders obtained at different temperatures using the Rietveld method. Data from this method showed the coexistence of cubic LiCoO2 (spinel) and rhombohedral (layered) structures when LiCoO2 was obtained at lower temperatures (400 and 500 degreesC). The single rhombohedral structure for LiCoO2 was obtained after post-heat treatment at 600 degreesC. The maximum energy capacity in the first discharge was 136 mA g(-1) for the composite electrode based on LiCoO2 obtained after heat treatment at 700 degreesC. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: LiCoO2; Rietveld method; lithium batteries; combustion synthesis